PENERAPAN MODEL PEMBELAJARAN TGT DISERTAI MOTIVASI BELAJAR MENINGKATKAN HASIL BELAJAR SENI RUPA SISWA SMA ADABIAH PADANG - Nilawati, Dr. Yahya, M.Pd., Drs. Wisdiarman, M.Pd. (Universitas Negeri Padang, 2018)
The aim of this research is to determine the effect of Team Game Tournament learning model and learning motivation on student learning outcomes in art learning at SMA Adabiah Padang. This research using quantitative type of quasi experiment by 2x2 factorial design. Data collection techniques used are learning motivation instrument and learning outcomes test instrument. The result of first hypothesis points tcount= 4,361 and ttable= 2,045 at alpha level = 0,05, these represent that tcount > ttable , then Hi is accepted. Second hypothesis points tcount= 4,037 and ttable= 2,306 at alpha level = 0,05, these represents that tcount > ttable , then Hi is accepted. Third hypothesis points tcount= 2,319 and ttable= 2,306 at alpha level = 0,05, these represent that tcount > ttable , then Hi is accepted. The conclusion according the result of the research obtained that the application of TGT model and learning motivation could to increase the learning outcomes of students in art learning at SMA Adabiah Padang.Keyword: Team Game Tournament learning model, learning motivation, learning outcomes, visual arts.